(untitled) (AYUSHDHARA, 2025)
Prevention of the disease is the need of the present era. Dincharya, Ritucharya, Nishacharya, Achara Rasayana, Sadvritta are some of the concepts comes under the heading of the Swasthavritta which primarily emphasis on the prevention of the diseases and preservation of health. Usha paan is one of the important components of the daily regimen (Dinacharya). This concept suggests to consume neutral water in amount of 8 Prasriti (640ml) in Bramha muhurta kala that is just before the sunrise. An attempt will be made to review the concept of Ushapana in detail after refereeing the various Ayurveda literature, published articles and possible justification of use of Tamra Patra Sthita jala for Ushapana will be made according to the prevailing contemporary science. For achieving this aim all online and offline material related to topic, modern text book has been reviewed. According to the classical reference Usha Paan is endowed with the advantages like improves the digestion, promote the bowel movement, detoxify body, and prevents from premature ageing by improving metabolism. Bhavaprakasha enumerates that different Patra to store the drinking water like Tamra Patra, Mrittika Patra, Kacha Patra etc. According to the Bhavamishra it water stored in different vessels will have different attributes like water stored in Tamra Patra has the quality of Pittakapha Shamaka and Lekhana when it is consumed in the season like Hemant, Shishira Vasant and Sharad Ritu. In present time people are very much fond of consuming water in the Tamra patra (Copper vessel) may be because of culture or costumes adopted by the ancestor or because of health benefit. Here the reviewed literature says that water stored in the tamara patra prevent the non-communicable metabolic disorders by enhance the metabolic activity and check the communicability of the water borne diseases by antimicrobial effect. Hence the concept of Ushapana in Tamra patra elaborated in the Bhavaprakasha is relevant in present ear.